EXPLORING DIGITAL PROFESSIONAL LEARNING ECOSYSTEMS: TRANSFORMING TEACHER COMPETENCY DEVELOPMENT POLICIES IN PRIVATE MADRASAS - Jejen Musfah; Sita Ratnaningsih; Fachri Aldin; Hasan Baharun (Nurul Jadid University, 2026)
The rapid expansion of digital education requires teacher competency development to move beyond fragmented training toward sustainable professional learning ecosystems. However, private madrasas continue to exhibit substantial disparities in teachers' digital competency outcomes. suggesting that existing policies have not effectively transformed professional development into institutional learning ecosystems. This study employed a qualitative multiple-case study design. Data were collected through in-depth interviews, observations, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three major transformations. First, teacher competency development policies have shifted from fragmented training initiatives toward digital professional learning ecosystems that promote continuous learning and collaborative knowledge sharing. Second, adaptive leadership emerged as the primary driver of policy transformation through strategic supervision, institutional resource allocation, and collaborative professional learning. Third, policy implementation remains constrained by limited institutional readiness, disparities in teachers' digital competencies, dependence on externally driven professional development, and weak professional learning cultures, resulting in uneven policy transformation across private madrasas.